2014
DOI: 10.1103/physrevb.89.214110
|View full text |Cite
|
Sign up to set email alerts
|

Role of the mesoscale in migration kinetics of flat grain boundaries

Abstract: Classical molecular dynamics simulations of bicrystalline systems are a commonly used tool for exploring the migration of grain boundaries. Most simulation work to date has focused on measuring the mobility of grain boundaries, assuming it to be an intrinsic property of a boundary of a given geometry.Here we present results from simulations of the migration of a typical high-angle grain boundary that show that the concept of intrinsic mobility fails for defect-free, flat boundaries of the type frequently simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 50 publications
2
47
0
Order By: Relevance
“…The periodic boundary conditions can also introduce artificial correlations within the grain boundary plane. As shown recently, these artificial correlations can alter the migration mechanisms if the lateral supercell dimensions are too small [14]. Extensive benchmarks showed that this is less of a problem for our nonsymmetric grain boundary structures where the small misorientation angles from the symmetric boundary result in large lateral dimensions of the CSL unit cells.…”
Section: Simulation Methodsmentioning
confidence: 68%
See 3 more Smart Citations
“…The periodic boundary conditions can also introduce artificial correlations within the grain boundary plane. As shown recently, these artificial correlations can alter the migration mechanisms if the lateral supercell dimensions are too small [14]. Extensive benchmarks showed that this is less of a problem for our nonsymmetric grain boundary structures where the small misorientation angles from the symmetric boundary result in large lateral dimensions of the CSL unit cells.…”
Section: Simulation Methodsmentioning
confidence: 68%
“…The mesoscale island nucleation model proposed in Ref. [14] accurately reproduces the temperature dependence of the velocity below the roughening temperature using only two fitting parameters [see the dashed lines in Fig. 3(a)].…”
Section: B Migration Kineticsmentioning
confidence: 79%
See 2 more Smart Citations
“…The coupling factor β = d m characterizes this migration. Despite experimental investigations [7][8][9] and recent theoretical studies [10][11][12][13][14][15][16], the details of the shear-coupled migration mechanisms remain poorly known.…”
Section: Introductionmentioning
confidence: 99%